Molecular Understanding of the Surface-Enhanced Raman Spectroscopy Salivary Fingerprint in People after Sars-COV-2 Infection and in Vaccinated Subjects - Francesca Rodà; Alice Gualerzi; Silvia Picciolini; Luana Forleo; Valentina Mangolini; Roberta Mancuso; Simone Agostini; Rudy Alexander Rossetto; Paola Pierucci; Paolo Innocente Banfi; Marzia Bedoni (Chemosensors, 2024)
The rapid spread of SARS-COV-2 and the millions of worldwide deaths and hospitalizations have prompted an urgent need for the development of screening tests capable of rapidly and accurately detecting the virus, even in asymptomatic people. The easy collection and the biomarker content of saliva, together with the label-free and informative power of surface-enhanced Raman spectroscopy (SERS) analysis have driven the creation of point-of-care platforms capable of identifying people with COVID-19. Indeed, different salivary fingerprints were observed between uninfected and infected people. Hence, we performed a retrospective analysis of SERS spectra from salivary samples of COVID-19-infected and -vaccinated subjects to understand if viral components and/or the immune response are implicated in spectral variations. The high sensitivity of the proposed SERS-based method highlighted the persistence of molecular alterations in saliva up to one month after the first positive swab, even when the subject tested negative for the rapid antigenic test. Nevertheless, no specific spectral patterns attributable to some viral proteins and immunoglobulins involved in COVID-19 infection and its progression were found, even if differences in peak intensity, presence, and position were observed in the salivary SERS fingerprint.